2019
DOI: 10.1088/1742-6596/1341/3/032005
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and activity of N-(o-tolyl)caffeamide and N-(o-tolyl)-p-coumaramide against P388 leukemia murine cells

Abstract: Ester derivatives of p-hydroxycinnamic compounds have high anticancer activity. However, the ester compounds usually easier to be decomposed than their amide derivates, so the ester compounds have a low potential to be applied as anticancer. In this research, the amide derivatives of caffeic and p-coumaric acids have been synthesized using o-tolylamine to give trans-N-(o-tolyl)caffeamide (5a) and trans-N-(o-tolyl)-p-coumaramide (5b), respectively. The products were characterized by FT-IR, 13C-NMR, and 1H-NMR m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…As shown in the docking study, it is due to the presence of an intramolecular hydrogen bond between the adjacent hydroxyl groups, which can stabilize the structure after releasing hydrogen radicals. This result is consistent with the previous report related to the comparison of anticancer activity between caffeamide and p-coumaramide (Firdaus et al, 2019). Meanwhile, compared to the activity of p-coumaramide that was isolated from Kleinhovia Hospita L. (IC 50 of 44.00 μg/ml) (Firdaus et al, 2014) and N-feruloyl morpholine which previously synthesized (IC 50 of 46.67) (Firdaus et al, 2017), compound 6a was considerably more active.…”
Section: Activity Against P388 Leukemia Murine Cellssupporting
confidence: 94%
“…As shown in the docking study, it is due to the presence of an intramolecular hydrogen bond between the adjacent hydroxyl groups, which can stabilize the structure after releasing hydrogen radicals. This result is consistent with the previous report related to the comparison of anticancer activity between caffeamide and p-coumaramide (Firdaus et al, 2019). Meanwhile, compared to the activity of p-coumaramide that was isolated from Kleinhovia Hospita L. (IC 50 of 44.00 μg/ml) (Firdaus et al, 2014) and N-feruloyl morpholine which previously synthesized (IC 50 of 46.67) (Firdaus et al, 2017), compound 6a was considerably more active.…”
Section: Activity Against P388 Leukemia Murine Cellssupporting
confidence: 94%
“…The absorption band is also supported by the absorption band at wavenumbers 1213.23 cm -1 and 1114.86 cm -1 from C-O. The absorption bands at 2835.36-2981.95 cm -1 and 1431.18 and 1373.32 cm -1 originated from the CH3 group (Firdaus et al, 2019). All absorption bands correspond to the structure of compound 1b shown in Figure 6.…”
Section: Synthesis Of Compound 1bmentioning
confidence: 61%
“…), 1602.85 dan 1508.41 cm -1 (C=C Ar), 2943.37 dan 2858.51 cm -1 (C-H sat. ), 1369.46 dan 1444.68 cm -1 (methyl) (Firdaus et al, 2019). This explanation is in accordance with the structure of compound 3c in Figure 6.…”
Section: Indo Chim Actamentioning
confidence: 96%
See 1 more Smart Citation
“…The two most abundant compounds in the aromatic ginger essential oil were trans-ethyl-pmethoxycinnamate and trans-ethyl cinnamate [1][2]5]. Ethyl-p-methoxycinnamate and its derivatives had many benefits, including as anticancer [6][7][8], anti-inflammatory [9][10], anti-tuberculosis [11], anti-neoplastic [12], antimicrobe [13], and antidiabetic [14] agents. The study of K. galanga L. extract as an antidiabetic using the Gavage method every day for one month found that diabetic rats before and after treatment with K. galanga L. extract showed a significant difference in reducing the amount of blood glucose [15].…”
Section: ■ Introductionmentioning
confidence: 99%